Senescence-Associated Pro-inflammatory Cytokines and Tumor Cell Plasticity - Vernot, Jean Paul (Frontiers in Molecular Biosciences, 2020)
The well-recognized cell phenotypic heterogeneity in tumors is a great challenge for cancer treatment. Dynamic interconversion and movement within a spectrum of different cell phenotypes (cellular plasticity) with the acquisition of specific cell functions is a fascinating biological puzzle, that represent an additional difficulty for cancer treatment and novel therapies development. The understanding of the molecular mechanisms responsible for moving or stabilizing tumor cells within this spectrum of variable states constitutes a valuable tool to overcome these challenges. In particular, cell transitions between epithelial and mesenchymal phenotypes (EMT-MET) and de-and trans-differentiation processes are relevant, since it has been shown that they confer invasiveness, drug resistance, and metastatic ability, due to the simultaneous acquisition of stem-like cell properties. Multiple drivers participate in these cell conversions events. In particular, cellular senescence and senescence-associated soluble factors have been shown to unveil stem-like cell properties and cell plasticity. By modulating gradually the composition of their secretome and the time of exposure, senescent cells may have differential effect not only on tumor cells but also on surrounding cells. Intriguingly, tumor cells that scape from senescence acquire stem-like cell properties and aggressiveness. The reinforcement of senescence and inflammation by soluble factors and the participation of immune cells may provide a dynamic milieu having varied effects on cell transitions, reprogramming, plasticity, stemness and therefore heterogeneity. This will confer different epithelial/mesenchymal traits (hybrid phenotype) and stem-like cell properties, combinations of which, in a particular cell context, could be responsible for different cellular functions during cancer progression (survival, migration, invasion, colonization or proliferation). Additionally, cooperative behavior between cell subpopulations with different phenotypes/stemness functions could also modulate their cellular plasticity. Here, we will discuss the role of senescence and senescence-associated pro-inflammatory cytokines on the induction of cellular plasticity, their effect role in establishing particular states within this spectrum of cell phenotypes and how this is accompanied by stem-like cell properties that, as the epithelial transitions, may also have a continuum of characteristics providing tumor cells with functional adaptability specifically useful in the different stages of carcinogenesis.